2021
DOI: 10.1097/ico.0000000000002827
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topical Cyclosporine 0.1% in Therapeutic Penetrating Keratoplasty for Fungal Keratitis

Abstract: The efficacy and safety of topical cyclosporine 0.1% in preventing early graft failure after therapeutic penetrating keratoplasty (TPK) in eyes with fungal keratitis were evaluated.Methods: This prospective case series included patients with fungal keratitis undergoing TPK from May to December 2019 who were treated with cyclosporine A 0.1% eye drops (tCSA group). We compared the outcome with a historical cohort of patients who were treated conventionally (CT group) with topical prednisolone acetate 1% eye drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…However, its use can potentiate and exacerbate the progression of fungal infections; hence, it must not be commenced until a causative agent is found and/or the patient has shown a favourable response to antibiotic/antifungal therapy [6,51]. An alternative treatment to control inflammation associated with fungal keratitis is topical cyclosporin, a calcineurin inhibitor and antifungal metabolite with antifungal properties [52]. It has been validated in the use of increasing corneal graft survival post penetrating keratoplasty for fungal keratitis as well as being synergistically combined with azole agents in treating resistant fungi [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, its use can potentiate and exacerbate the progression of fungal infections; hence, it must not be commenced until a causative agent is found and/or the patient has shown a favourable response to antibiotic/antifungal therapy [6,51]. An alternative treatment to control inflammation associated with fungal keratitis is topical cyclosporin, a calcineurin inhibitor and antifungal metabolite with antifungal properties [52]. It has been validated in the use of increasing corneal graft survival post penetrating keratoplasty for fungal keratitis as well as being synergistically combined with azole agents in treating resistant fungi [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…This is currently the most common approach. We found promising results of using topical 0.5% and 0.1% cyclosporin A (CsA) instead of steroids in early postoperative treatment after TPK in fungal keratitis [ 140 , 141 ]. In some studies, the combination of azoles with CsA showed synergistic fungicidal effect [ 142 , 143 ].…”
Section: Therapeutic Keratoplastymentioning
confidence: 99%
“…26 However, human studies of calcineurin inhibitors for fungal keratitis are limited. 27 The role of corticosteroids after therapeutic penetrating keratoplasty for fungal keratitis is unclear because steroids may help prevent immune rejection but may also increase the risk of recurrent infection. Several reports advocate withholding steroids for 1 to 2 weeks after surgery and only instituting steroid treatment if no signs of recurrent infection have developed during that period.…”
Section: Fungal Keratitismentioning
confidence: 99%